Counseling and Examination of Gastrointestinal Parasites in Horses in Payakumbuh City - Engki Zelpina; Prima Silvia Noor; Sujatmiko; Delli Lefiana (Jurnal Pengabdian Masyarakat Bestari, 2023)
This Community Service is carried out from August to September 2021 in the Horse breeding area in Payakumbuh City in the form of counseling and examination of horse feces in the laboratory with the aim of this program being to provide knowledge to horse owners and stool examination in the laboratory to find out gastrointestinal parasites. This program was carried out by visiting the location of the horse stables and taking the feces of 50 horses. From the results of laboratory examinations, horses infected with gastrointestinal parasites were 82% (41/50), the prevalence was higher in mares 70% and stallions 12%. Although clinically the horse showed healthy symptoms but still had gastrointestinal parasites. It is hoped that from this activity horse breeders can improve management of maintenance, feed and also the health of horse livestock.